Lung transplantation - Afonso Júnior,José Eduardo (2015)
ABSTRACT Lung transplantation is a globally accepted treatment for some advanced lung diseases, giving the recipients longer survival and better quality of life. Since the first transplant successfully performed in 1983, more than 40 thousand transplants have been performed worldwide. Of these, about seven hundred were in Brazil. However, survival of the transplant is less than desired, with a high mortality rate related to primary graft dysfunction, infection, and chronic graft dysfunction, particularly in the form of bronchiolitis obliterans syndrome. New technologies have been developed to improve the various stages of lung transplant. To increase the supply of lungs, ex vivo lung reconditioning has been used in some countries, including Brazil. For advanced life support in the perioperative period, extracorporeal membrane oxygenation and hemodynamic support equipment have been used as a bridge to transplant in critically ill patients on the waiting list, and to keep patients alive until resolution of the primary dysfunction after graft transplant. There are patients requiring lung transplant in Brazil who do not even come to the point of being referred to a transplant center because there are only seven such centers active in the country. It is urgent to create new centers capable of performing lung transplantation to provide patients with some advanced forms of lung disease a chance to live longer and with better quality of life.